The Use for beIN Sport channels to watch the Qatar world Cup 2022 and the earned sports gratification A field study on sports information and communication students at the University of M’sila - HAMICHE, Youcef (sports creativity, 2023)
The study aimed to know the sports informative, cognitive, and analytical needs that are earned for sports information and communication students , after they used beIN Sport channels to watch the 2022 World Cup., In this study, the researcher uses the comprehensive survey, and he relies on the descriptive method, he used the questionnaire as a data collection tool, this tool has been applied to all members of the study society, The study data is analyzed by using statistical and analytical method. The results show : Most of the respondents watched the 2022 World Cup via beIN Sport channels, they allocated up to 3 hours to watching, whether inside or outside the home ; beIN Sport channels achieved many news gratifications for the respondents, such as press coverage of the World Cup 2022, cognitive gratifications, Like defining football law, And analytical gratification through the preparation of analytical programs for the World Cup and match analysis.